PENGUATAN KETERAMPILAN ABAD 21 GURU MIPA DALAM PEMBELAJARAN MIPA: TINJAUAN 4C, HOTS, DAN TPACK - P, Ria Indria; Mulyati, Sri; Rahayu, Lusy; Purnamasari, Risa; Karim, Nuzulia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Contemporary educational transformation requires educators, particularly in Mathematics and Natural Sciences (MIPA), to master competencies that are adaptive to global changes, technological innovation, and the learning needs of the digital generation. Twenty-first-century competencies encompass critical thinking, creativity, collaboration, and communication (4C), Higher Order Thinking Skills (HOTS), and Technological Pedagogical Content Knowledge (TPACK), which are considered fundamental in creating meaningful MIPA learning. The purpose of this article is to analyze the strategic importance of developing twenty-first-century competencies for MIPA educators within the Indonesian education system. A literature review approach was employed to examine research publications and educational regulations published between 2020 and 2025. The findings indicate a disparity between the expectations of twenty-first-century learning and the actual capacity of MIPA educators, particularly in facilitating HOTS and implementing pedagogy-based technology. The implementation of the Merdeka Curriculum, character building through the Pancasila Student Profile, and the performance of Indonesian students in science and mathematics literacy in global assessments such as PISA strengthen the argument for the importance of enhancing MIPA educators' capacity in twenty-first-century skills. This article proposes continuous professional development, educator communities of practice, and technology optimization through the TPACK framework as primary approaches to competency enhancement. ABSTRAK Transformasi pendidikan kontemporer mengharuskan pendidik, terutama dalam bidang Matematika dan Ilmu Pengetahuan Alam (MIPA), menguasai kompetensi yang adaptif terhadap perubahan global, inovasi teknologi, dan kebutuhan pembelajaran generasi digital. Kompetensi abad ke-21 mencakup berpikir kritis (critical thinking), kreativitas (creativity), kolaborasi (collaboration), komunikasi (communication) atau disingkat 4C, keterampilan berpikir tingkat tinggi (Higher Order Thinking Skills/HOTS), dan pengetahuan teknologi pedagogi konten (Technological Pedagogical Content Knowledge/TPACK) yang dianggap fundamental dalam menciptakan pembelajaran MIPA bermakna. Tujuan penulisan artikel ini ialah menganalisis kepentingan strategis pengembangan kompetensi abad ke-21 bagi pendidik MIPA dalam sistem pendidikan Indonesia. Pendekatan kajian literatur digunakan untuk menelaah publikasi riset dan regulasi pendidikan yang terbit antara tahun 2020 hingga 2025. Temuan mengindikasikan adanya disparitas antara ekspektasi pembelajaran abad ke-21 dengan kapasitas riil pendidik MIPA, terutama pada aspek fasilitasi HOTS dan penerapan teknologi berbasis pedagogi. Pelaksanaan Kurikulum Merdeka, pembentukan karakter melalui Profil Pelajar Pancasila, dan performa literasi sains serta matematika siswa Indonesia dalam evaluasi global seperti PISA memperkuat argumentasi pentingnya peningkatan kapasitas pendidik MIPA dalam keterampilan abad ke-21. Artikel ini mengusulkan pengembangan keprofesian berkelanjutan, komunitas praktik pendidik, dan optimalisasi teknologi melalui kerangka TPACK sebagai pendekatan utama dalam peningkatan kompetensi.